Implementasi Layanan Berbasis Jamaah (LASISMA) Menggunakan Akad Al-Qardhul Hasan dan Sistem Tanggung Renteng di BMT NU Cluring - Sidqi, Ahmad Yusron; Habibulloh, Habibulloh; Hidayat, Balya (Jurnal Manajemen dan Ilmu Administrasi, 2025)
This study aims to: (1) examine the implementation of the Layanan Simpan Pinjam Mandiri (LASISMA) financing program using the qardhul hasan contract at BMT NU Cluring Branch; (2) analyze the tanggung renteng (joint liability) system applied in LASISMA financing; and (3) identify the profit contribution received by BMT NU Cluring from its members. This research employs a qualitative approach with data collection techniques including in-depth interviews, observation, and documentation. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldana (2014), which consists of data condensation, data display, and conclusion drawing/verification. The findings reveal that the implementation of LASISMA financing with the qardhul hasan contract is carried out in accordance with sharia principles and focuses on empowering members’ economies through interest-free loans without profit margins. The tanggung renteng system has proven effective in minimizing default risk by emphasizing collective responsibility among group members. Although qardhul hasan financing does not generate direct financial profit, it strengthens member loyalty, expands the membership network, and enhances the social image of BMT NU Cluring. Indirectly, this contributes positively to the institution’s profitability and sustainability. This study affirms that social missions and financial sustainability can coexist when managed strategically in alignment with sharia principles